Entre a crise e a notícia: as estratégias organizacionais da Air France e a construção do acontecimento “voo 447” pela mídia impressa brasileira e francesa - Pérsigo, Patrícia Milano (2011)
This dissertation studies the strategies of an organization under a crisis situation in the construction of a journalistic occurrence in a mediatized society. There are constant challenges to be overcome by organizations, visibility processes are constantly being changed by new technologies advent, changes in the media s role and the appropriation of their approaches by various social fields on their daily practices. This are just some changes which require reflection about crisis management strategies adopted until nowadays. The organizational crises present themselves as very explored occurrences by the media. These events are characterized by the disruption of everyday s life, mainly by its unpredictability, that's the fact that arouses wide interest in the media field. With the method of content analysis (Bardin, 1977) we adopted as our empirical object the crisis faced by Air France with the tragedy of Flight 447, analyzing news in Folha de São Paulo and Le Monde s newspapers. Thus, we persue to study the impact of this crisis in French and Brazilian media, to verify the sources used by the media in the occurrence construction, as well as the position given to the organization in the news published, identifying the organization's strategies to mitigate the incident, and understanding the strategic nature of the interface press -company in crisis situations in news production. So, as a result of this research, we concluded that in this crisis the organization has adopted and maintained a concise and objective position in addition to technical measures taken to circumvent the situation. This triggered another kind of relationship with the media, where what was witnessed was not an Air France's image crisis, but on the other hand, the occurrence "447" was explored as a tragedy. So, what stands out in this scenario is that between the crisis and the news, the news prevailed.